ANALISIS PENGARUH FAKTOR PRODUKSI TERHADAP PRODUKTIVITAS JAMUR TIRAM DI DESA GENTING KECAMATAN JAMBU KABUPATEN SEMARANG - DWI AGUSTIN RAHMAWATI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2019)
The purpose of this research is to know the influence of land factor, baglog number, amount of labor, lime use, pesticide usage, temperature, humidity, watering frequency, weather, environmental hygine, pest to productivity of oyster mushroom and analyze the type of wood powder as media growing oyster mushrooms faster growth. The research was conducted in the Genting village of Jambu district of Semarang. This research is quantitative descriptive. Sampling using purposive sampling technique with 40 respondents. The data analysis technique used is double liniear regression method. The results showed that the factors that influence the productivity og oyster mushrooms are statistically the amount of baglog, tempereture, frequency of wathering, weather, cleanliness of pest environment. While the variable land area, the amount of labor, the use of lime, the use of pesticides, moisture has no significant effect on the productivity of oyster mushrooms. As a medium, the mushrooms will grow faster on media direved from softwood powder typr compared to the type of hardwood powder.